Coverage of In Situ Climatological Observations in the World's Mountains - Thornton, James M.; Pepin, Nicholas; Shahgedanova, Maria; Adler, Carolina (Frontiers in Climate, 2022)
Many mountainous environments and ecosystems around the world are responding rapidly to ongoing climate change. Long-term climatological time-series from such regions are crucial for developing improving understanding of the underlying mechanisms driving such changes, and ultimately delivering more reliable future impact projections for environmental managers and other decision makers. Whilst it is already established that high elevation regions tend to be comparatively under-sampled, detailed spatial and other patterns in the coverage of mountain climatological data have not yet been comprehensively assessed on a global basis. To begin to address this deficiency, we analyse the coverage of records associated with the mountainous subset of the Global Historical Climatological Network-Daily (GHCNd) inventory with respect to space, time, and elevation. Three key climate-related variables -- air temperature, precipitation, and snow depth -- are considered across 292 named mountain ranges. Several additional datasets were then introduced to characterise data coverage relative to topographic, hydrological, and socio-economic factors. Spatial mountain data coverage is found to be highly uneven, with especially low station densities in several ``Water Tower Units'' that were previously identified as having great hydrological importance to society. Several mountainous regions whose elevational distribution is severely undersampled by GHCNd stations are also identified, and mountain station density shown to be only weakly related to the human population or economic output of the corresponding downstream catchments. Finally, we demonstrate the capabilities of a script (provided in the Supplementary Information) to produce detailed assessments of individual records' temporal coverage and measurement quality information. Overall, this contribution should help international authorities and regional stakeholders alike to identify areas, variables, and other monitoring aspects that should be prioritised for investment in infrastructure and capacity. Finally, the transparent and reproducible approach taken enables the analysis to be rapidly repeated for subsequent versions of GHCNd, and may furthermore support similar analyses using other spatial reporting boundaries and/or environmental monitoring station networks.